Effect of the initial drop size distribution of monomer on the average molecular weight of polymer products - Bárkányi, Ágnes; Németh, Sándor; Lakatos, G. Béla (Acta Agraria Kaposváriensis, 2011)
In the paper suspension polymerization is investigated. In a typical suspension polymerization system the water-insoluble monomer is dispersed in the continuous aqueous phase by combining the intensive stirring with the use of a small amount of stabilizers. The process was studied by simulation using a computer program in MatLab environment. It was assumed that droplets of the same size break-up and coalesce continuously in the turbulent flow field generated by intensive stirring of the suspension. The volumes of droplets have been changed but their numbers were kept constant. The results of simulation revealed that the dispersion of monomer and of the soluble components in the polymerization process plays rather important role. When the process is started with an initial drop size distribution of monomer significant difference in the average molecular weight is observed compared with the initially mono-sized droplets.
Keywords: polymerization of vinyl chloride; population balance equation; momentum method; micromixing; drop size distribution